A systematic literature review of web-based tools application in ESL and EFL writing classes - Kassim, Asiah; Kassim, Hafizoah; Nik Mohd Alwi, Nik Aloesnita; Nordin, Mohd Shukri; Rahim, Mahdalela (Universiti Malaysia Pahang Al-Sultan Abdullah, 2024)
The 1990s saw the advent of internet use, eventually termed as web 1.0. Embracing this technological evolution, language learning classrooms have been using this digital tool in the teaching and learning processes. The paper systematically analysed the literature on this digital use for writing in ESL/EFL classes published between 1990 and 2023, aiming at identifying the most frequently used web-based tools in writing classes, exploring their facilitative features in developing learner’s writing skills and evaluating their effects on the development of varied writing types. Ninety-three articles retrieved from five major databases - Science Direct, Scopus, SpringerLink, Taylor & Francis and Web of Science - were analysed using the content analysis method. Findings revealed that writing classes in recent years have been primarily utilising social media channels, such as Facebook, collaborative authoring platforms, for example, Google Docs and data-driven learning tools like Corpus, optimising the interactive and interconnectedness of these applications. Further exploration disclosed the facilitative features contributed mainly by the interactive element of the web, enabling teaching and learning of writing to take place in and outside of the classroom. Discussions also highlighted certain facilitative features perused in relation to different types of writing. This review affirms the facilitative benefits of web technology in enhancing the learners’ writing skills. It concludes by suggesting future studies for the teaching and learning writing for ESL and EFL learners